2016
DOI: 10.1016/j.neuropsychologia.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Congruency of body-related information induces somatosensory reorganization

Abstract: Chronic pain and impaired tactile sensitivity are frequently associated with "blurred" representations in the somatosensory cortex. The factors that produce such somatosensory blurring, however, remain poorly understood. We manipulated visuotactile congruence to investigate its role in promoting somatosensory reorganization.To this aim we used the mirror box illusion that produced in participants the subjective feeling of looking directly at their left hand, though they were seeing the reflection of their righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 71 publications
5
19
0
Order By: Relevance
“…Alterations in the somatosensory cortex are thought to be behind the anomalous bodily experiences of people with CRPS (Flor et al, 1995, 1997; Maihöfner et al, 2003, 2004; McCabe et al, 2003; Pleger et al, 2005; Marinus et al, 2011) and previous studies using sensory feedback to manipulate people's body representations have linked their results to recalibration of somatosensory receptive fields (RF) in the somatosensory cortex (Taylor-Clarke et al, 2004; de Vignemont et al, 2005; Haggard et al, 2007; Cardinali et al, 2009, 2012; Cardini et al, 2011, 2012, 2013; Tajadura-Jiménez et al, 2012, 2016; Canzoneri et al, 2013a,b; Miller et al, 2014; Cardini and Longo, 2016). We suggest that the observed changes in body-representation in the current study may also indicate reorganization within the somatosensory cortex The observed changes in kinematics of gait may also support this suggestion, if it is considered that the control of body movements relies on somatosensory representations of body dimensions (Holmes and Spence, 2004; Maravita and Iriki, 2004; Cardinali et al, 2009; Tajadura-Jiménez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the somatosensory cortex are thought to be behind the anomalous bodily experiences of people with CRPS (Flor et al, 1995, 1997; Maihöfner et al, 2003, 2004; McCabe et al, 2003; Pleger et al, 2005; Marinus et al, 2011) and previous studies using sensory feedback to manipulate people's body representations have linked their results to recalibration of somatosensory receptive fields (RF) in the somatosensory cortex (Taylor-Clarke et al, 2004; de Vignemont et al, 2005; Haggard et al, 2007; Cardinali et al, 2009, 2012; Cardini et al, 2011, 2012, 2013; Tajadura-Jiménez et al, 2012, 2016; Canzoneri et al, 2013a,b; Miller et al, 2014; Cardini and Longo, 2016). We suggest that the observed changes in body-representation in the current study may also indicate reorganization within the somatosensory cortex The observed changes in kinematics of gait may also support this suggestion, if it is considered that the control of body movements relies on somatosensory representations of body dimensions (Holmes and Spence, 2004; Maravita and Iriki, 2004; Cardinali et al, 2009; Tajadura-Jiménez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to the present research, some of these studies have proposed that the altering of sensory cues related to one's body can result in reorganization within the somatosensory cortex (Taylor-Clarke et al, 2004; de Vignemont et al, 2005; Haggard et al, 2007; Cardinali et al, 2009, 2012; Cardini et al, 2011, 2012, 2013; Tajadura-Jiménez et al, 2012, 2016; Canzoneri et al, 2013a,b; Miller et al, 2014; Cardini and Longo, 2016). In relation to people with CRPS, it has been suggested that the lack of sensory input from the limb may contribute to the perpetuation of their BPD, as they are often reluctant to look at or touch their affected limb, choosing to position it in such a way that it is outside their field of view and even trying to avoid thinking about it (Lewis et al, 2007; Lewis and McCabe, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that visual-somatosensory conflict alters the perception (Bultitude, Juravle, & Spence, 2016; Folegatti, de Vignemont, Pavani, Rossetti, & Farnè, 2009) and neural processing of touch (Cardini & Longo, 2016). It is therefore possible that the recalibration found in Experiment 1 could be explained by illusion-related conflict between visual and somatosensory signals irrespective of tool use.…”
Section: Experiments 5: Sensory Conflictmentioning
confidence: 99%
“…However, the findings by Schaefer and colleagues (2004) leave open the possibility that even low-level stages of processing in SI may be modulated by tool use. To foreshadow our results, we found significant evidence that tool use (but not hand use) modulates the amplitude of the mid-latency P100 component, an index of multisensory models of the body (Cardini and Longo 2016).…”
mentioning
confidence: 52%
“…The mid-latency P100 component was calculated as the mean amplitude at CP1, CP3, P1, and P3 between 70 and 110 ms post-shock. The P100 is the earliest component to index visual-tactile integration (Sambo) and reflects the maintenance of a multisensory model of the body (Cardini and Longo 2016). It has known generators in SII and PPC (Forss et al 1994;Barba et al 2004).…”
Section: Erp Analysesmentioning
confidence: 99%